Research on the Application of Smart Site Management for Cross-regional Power Grid Project Based on the Basic Framework of Digital Power Grid. Issue 3 (February 2020) - Sun, Wencheng; Cheng, Wentao; Peng, Yuhui; Wang, Hongjie; Liu, Jianqiao; Zhang, Haoyu; Wang, Jian
Abstract: In order to further improve the infrastructure management level of power grid projects and promote the fine management and scientific organization of power grid projects. Based on the basic framework of digital power grid, this paper uses UAV remote sensing, geographic information system, 3D virtual simulation, mobile Internet, Internet of things, intelligent sensor and other technical means to build a intelligent management and control platform integrating monitoring, early warning, command and emergency response. Exploring the application scenarios in terms of project schedule, quality, safety, special project, and on-site Internet of things perception. Practice shows that the construction of the platform can effectively improve the overall control of the power grid construction site and all kinds of information control level and risk prevention and control capabilities..